Acousmatic Warfare: Staging Sound in the Play(game)house of A Midsummer Night's Dream - Cortes, Mayra (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2025)
Acousmatic warfare, the use of sound without a visible source as a means of force, is presented in Shakespeare’s A Midsummer Night’s Dream as sonic play akin to that of an innocuous, ephemeral play, game, or dream, prompting audiences to engage carefully with the play’s uncanny sonic effects. The staging of acousmatic sound makes possible the coexisting presence of both racialization and resistance. The inset play, Pyramus and Thisbe, presents a competitive and interactive play that both racializes and protects the artisan players by allowing them to use their authorial skills to stage sonic resistance against aristocratic powers.